Implementation of Mufrodat Learning Using Circle Congklak Media Based on Cooperative Learning Type TGT (Team Games Tournament) - dwi rahma Uswatun Hasanah Herpagel; Erni Zuliana; Asti Fauziah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
Arabic language learning at MIN 6 Bandar Lampung still needs to be strengthened, especially in terms of the vocabulary (mufrodat) mastery of sixth grade students. Based on the results of observations and interviews conducted on September 16, 2025, it was found that learning was still dominated by lecture methods and qawā'id wa tarjamah material with learning media that was not very varied or innovative. Teacher-centered learning causes students to tend to be passive, easily bored, and have low memory retention of mufrodat. This is reinforced by the results of the pretest, which showed that out of 30 sixth-grade students in class B, only 5 students (17%) achieved the Minimum Completion Criteria (KKM ≥ 70), while the other 25 students (83%) did not. The highest score was only 80 and the lowest was 24, indicating the need for more effective and contextual learning interventions. This study aims to improve the mastery of Arabic vocabulary (mufrodat) of sixth-grade students at MIN 6 Bandar Lampung through the implementation of Circle Congklak media based on the Team Games Tournament (TGT) cooperative learning model. The intervention was designed based on the principles of social constructivism and vocabulary acquisition theory, utilizing multimodal stimulation through modified traditional games. The research, which was conducted in two cycles (covering planning, action, observation, and reflection), used tests, observation, interviews, and documentation for data collection. The results of the study showed a significant increase in students' mastery of vocabulary in Arabic language learning. The percentage of learning completeness increased from 17% (5 students) on the pretest to 53% (16 students) in cycle I, and further increased to 87% (26 students) in cycle II. These findings indicate that the integration of the culturally contextual Circle Congklak game with the TGT structure succeeded in creating an active, enjoyable, and collaborative learning atmosphere. This approach effectively motivated students, increased engagement, and facilitated vocabulary acquisition. It was concluded that TGT-based Circle Congklak media is an effective innovative strategy for improving Arabic vocabulary learning outcomes at the elementary school level.